Civil Society and Prospects for Enhancing the Values of Citizenship and Development - شبيطة , علي; بن هدية, مفتاح (Milev Journal of Research and Studies, 2023)
Civil society is a significant institution encompassing social, political, cultural, and economic dimensions in which citizens voluntarily engage to serve various aspects of societal concerns. This engagement, referred to as civic participation, reflects the effectiveness of societal involvement within its framework. It is a central issue that garners wide attention in democratic societies, as it nurtures the concept of participatory democracy in building political and social systems. Moreover, civil society endeavors to promote positive citizenship values that seek to enhance and advance society in various aspects, reinforcing its diverse systems. Amidst this context, the present research paper underscores the importance of focusing on the supportive frameworks for civic participation, such as civil society. Specifically, this study examines several elements that contribute to the research topic, tracing the historical trajectory of civic engagement through civil society in Algeria. It investigates the role of civil society as a mechanism for guiding citizens and fostering a culture of participation, while also identifying key obstacles impeding the growth of civic engagement through involvement and activities within various civil society organizations. Ultimately, the research aims to assess whether civil society truly influences the creation of a social dynamism that enhances citizenship values, a sense of belonging, and active contributions to the development and growth of the societal structure across different dimensions.